Pengaruh Motivasi Mitra Terhadap Keberlangsungan Usaha Mikro Kecil Menengah “Mommy Snack” - Fidelis, Bernardto; Valencia, Cahyani; Wiryawan, Fiona; Rintis, Jordan Joel; Lazuardi, Natalie; Wibowo, Rashif Ardi; Nurhayati*, Nurhayati (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This research is motivated by that high motivation of “mitra” in carrying out her daily business operation. This activity aims to find out how the business motivation within the micro, small and medium enterprises (SMEs) “do-er (pelaku)”, namely in the packaged snacks sector, will affect performance and the sustainability of a business. Two subjects that the researcher would like to raise are the kinds of partner’s motivation and its effect on the business sustainability. In conducting this research, the literature review used is the theories of business motivation, factors that influence motivation, and the affect of motivations on business continuity. The research method used is by library study, observation, and interview. The researcher concluded that the forms of motivation that have been carried out by partners have proven to have a big influence in providing results, namely the sustainability of the partners' business up to now.